Global collaborative patents - Sari Pekkala Kerr; William R. Kerr (Bank of Finland, 2017)
We study the prevalence and traits of global collaborative patents for U.S. public companies, where the inventor team is located both within and outside of the United States. Collaborative patents are frequently observed when a corporation is entering into a new foreign region for innovative work, especially in settings where intellectual property protection is weak. We also connect collaborative patents to the ethnic composition of the firm s U.S. inventors and cross-border mobility of inventors within the firm. The inventor team composition has important consequences for how the new knowledge is exploited within and outside of the firm.
URN:NBN:fi:bof-201701131012
Keywords: O32; F02; F22; F23; F60; J15; O19; O3; O33; O34; 330